EFEKTIFITAS KEBIJAKAN PEMERINTAH TERHADAP PAJAK PERHOTELAN DALAM PENINGKATAN PAD DI ERA OTONOMI - Rochmansyah Setiono; Arifin Tumuhulawa; Marten Bunga (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
This study analyzes government policies towards hotel taxes in increasing Regional Original Revenue (LOR) in the era of regional autonomy. The results show that the policy has not been effective, although hotel taxes contribute to LOR with fluctuations. Inhibiting factors include ineffective tax officers, inadequate facilities and facilities, and taxpayer communities that avoid taxes. Local governments must set explicit provisions and improve the collection and collection of unpaid taxes. Intensive socialization of hotel tax regulations is also needed to increase taxpayer public awareness and service quality